Maximum power point charge controller for DCDC power conversion in solar PV system - Uddin, Md. Nasir; Rashid, Muhammad Mahbubur; Aziz, M. A.; Nithe, N. A. (Global Journals Inc. (USA), 2016)
A charge controller that includes an input interface that receives input DC electrical signals. A converter section converts the input DC electrical signals to output DC electrical signals. Control means is operably coupled to the converter section. The control means includes means for operating the converter section at an estimated maximum power point of the input DC electrical signals. The estimated maximum power point is derived by a novel control scheme that quickly adapts to changing conditions and thus affords optimum energy harvest from the source and improved energy conversion efficiencies.